2023
DOI: 10.3390/ani13091503
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing (RNA-Seq) Analysis Reveals Liver Lipid Metabolism Divergent Adaptive Response to Low- and High-Salinity Stress in Spotted Scat (Scatophagus argus)

Abstract: Spotted scat (Scatophagus argus) can tolerate a wide range of salinity fluctuations. It is a good model for studying environmental salinity adaptation. Lipid metabolism plays an important role in salinity adaptation in fish. To elucidate the mechanism of lipid metabolism in the osmoregulation, the liver transcriptome was analyzed after 22 d culture with a salinity of 5 ppt (Low-salinity group: LS), 25 ppt (Control group: Ctrl), and 35 ppt (High-salinity group: HS) water by using RNA sequencing (RNA-seq) in spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…The decrease in UGT gene expression disrupts organismal homeostasis in response to hypoxic stress [39]. It is speculated that reducing the metabolism of small lipophilic molecules, such as steroid hormones, might have contributed to this phenomenon, as evidenced by the spotted scat [40]. This difference may be due to the fact that the species-specific patterns and precise mechanisms remain to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in UGT gene expression disrupts organismal homeostasis in response to hypoxic stress [39]. It is speculated that reducing the metabolism of small lipophilic molecules, such as steroid hormones, might have contributed to this phenomenon, as evidenced by the spotted scat [40]. This difference may be due to the fact that the species-specific patterns and precise mechanisms remain to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the adipocytokine signaling pathway was found to play a significant role in high-salinity stress in spotted scat (Scatophagus argus), with upregulation of the following genes: g6pc1, socs1, socs3, adipor2, pck1, and ppara in liver of fish treated in high salinity conditions (77). Our study revealed ten differentially expressed genes (or isoforms) with opposite directions of regulation in gynogenetic and sexual fish after D. pseudospathaceum infection, with some of them (especially nfkbia, g6pc1, socs3) already revealed by previous studies [e.g (74)(75)(76)(77)]. Several DEGs enriched within the adipocytokine signaling pathway belonging to endocrine system in our study of gibel carp were also reported within the next endocrine system pathwayspecifically, the insulin signaling pathway (socs3a, g6pc, g6pc1a.2, irs2a and irs2b).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, research on Scatophagus argus under salt stress found that both high and low amounts of salt stress led to a significant downregulation of genes (cept1 and pla2g4a) associated with glycerophospholipid metabolism. This indicates a reduced efficiency in the conversion of phosphatidylserine, and changes in cell membrane structure and energy storage may occur for the organism to adapt to different salinity conditions [37]. Therefore, we hypothesize that the disruption of the glutamine metabolism pathway leads to more severe damage to crucian carp cell membranes.…”
Section: Oxidative Stressmentioning
confidence: 97%